THE LANGUAGE OF THE EXILED DURING THE INDEPENDENCE WAR - Gómez Baeza, Nicolás; Retamal Navarro, Felipe; Rivas Rodríeguez, Javier (Revista de Historia Social y de las Mentalidades, 2011)
After exposing briefly the main theoretical  framework of the political thinking and  metaphorology, the article analyses the main  features of the language used by the exiled  -under the charge of being a menace to the  independentist movement - in the letters  directed to the political authorities of the  newborn republic twice during the uprising  emancipatory - in the year 1813, during the  ruling of José Miguel Carrera, and between  1817 and 1818, during the ruling of Bernardo O`Higgins. Afterwards, it is concluded that along the  process there was an important transformation  of the discursive repertoire used by the  exiled, from a predominance of sensitive  body experience as a talk resource field to  a predominance of the resources linked to  legality and the praising of the Americanist  cause.
Keywords: History of Political Discourse; Metaphorology; Discursive repertoire of the exiles; Independence process in Chile